2011
DOI: 10.1007/s13244-010-0057-0
|View full text |Cite
|
Sign up to set email alerts
|

Dual- and multi-energy CT: approach to functional imaging

Abstract: The energy spectrum of X-ray photons after passage through an absorber contains information about its elemental composition. Thus, tissue characterisation becomes feasible provided that absorption characteristics can be measured or differentiated. Dual-energy CT uses two X-ray spectra enabling material differentiation by analysing material-dependent photo-electric and Compton effects. Elemental concentrations can thereby be determined using three-material decomposition algorithms. In comparison to dual-energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
120
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(126 citation statements)
references
References 55 publications
0
120
0
1
Order By: Relevance
“…25 Multi-energy imaging approaches functional imaging by identifying materials with an increased accuracy. 27 Dual energy can be used to lessen metal artefacts by reconstructing images with optimal energy levels. However, in our study, we found only slight benefit of using dual energy in its current state.…”
Section: Discussionmentioning
confidence: 99%
“…25 Multi-energy imaging approaches functional imaging by identifying materials with an increased accuracy. 27 Dual energy can be used to lessen metal artefacts by reconstructing images with optimal energy levels. However, in our study, we found only slight benefit of using dual energy in its current state.…”
Section: Discussionmentioning
confidence: 99%
“…Many summary articles [2][3][4] exist to provide thorough basic and moderately advanced understanding of the associated principles and mathematics.…”
Section: Principlesmentioning
confidence: 99%
“…Typically encountered materials such as calcium, iodine, and water possess sufficiently different linear attenuation at low and high energies to allow for good discrimination (primarily based on the lower useful energies where the photoelectric effect dominates). However, materials with very similar attenuation curves, such as soft tissue, fat and water, are more problematic and require more advanced analytical techniques (beam prefiltering, three compartment analysis [4]). …”
Section: Principlesmentioning
confidence: 99%
“…This makes it possible to analyse the iodine uptake of tissues or organs directly and effectively reflect the blood perfusion state of tissues or organs. 6,8 A recent study 9 has investigated the performance of spectral CT in depicting the superior mesenteric artery (SMA). It is of great importance to explore the diagnostic value of sDECT in SMAE.…”
Section: Introductionmentioning
confidence: 99%